Mobility in an Enlarging European Union: Projections of Potential Flows from EU's Eastern Neighbors and Croatia - Michael Fertig; Martin Kahanec (Institute for the Study of Labor (IZA), 2013)
This study evaluates potential migration flows to the European Union from its eastern neighbors and Croatia. We perform out-of-sample forecasts using an adaption of the model of Hatton (1995) to time series cross-sectional data about post-enlargement migration flows following the EU's 2004 enlargement. We consider two baseline policy scenarios, with and without accession of sending countries to the EU. Our results show that migration flows are driven by migration costs and economic conditions, but the largest effects accrue to policy variables. In terms of the predicted flows: (i) we can expect modest migration flows in case of no liberalization of labor markets and only moderately increased migration flows under liberalization; (ii) after an initial increase following liberalization, migration flows will subside to long run steady state; (iii) Ukraine will send the most migrants; and (iv) the largest inflows in absolute terms are predicted for Germany, Italy and Austria, whereas Ireland, Denmark, Finland and again Austria are the main receiving countries relative to their population.
Keywords: F22; C23; C53; 330; migration; free movement of workers; European Union; Eastern Partnership; EU enlargement; migration potential; out-of-sample forecasting